LITHOSPHERIC STRESS FIELD AS A CONTROL OVER SEISMOGENIC FAULT PARAMETERS AND EARTHQUAKE MAGNITUDES - Lunina O.V. (My University, 2001)
Relations between the length of seismic rupture, amount of slip, and magnitude of earthquakes are investigated as a function of slip mechanism (normal, reverse, or strike slip) formed in different stress fields. The parameters of seismic strike-slip faults are closely correlated with earthquake magnitudes in any stress field. The relationships for normal and reverse faults are the most regular if they evolve under extension and compression, correspondingly, or in transtension and transpression fields. Compression is the most complicated environment for faulting of any kinematics. The results of the study can be used in paleoseismicity reconstructions.